Enhancement of Resistance Switching in Electrodeposited Co-ZnO Films. (31st July 2012) - Chu, Dewei; Younis, Adnan; Li, Sean
Abstract : High quality Co-doped ZnO films were prepared with electrodeposition. The correlation among the surface morphology, lattice structure, Co-dopant distribution, and resistance switching properties of the as-deposited films were investigated. It is found that resistance switching behaviour could be manipulated by controlling the composition of Co in the ZnO films. The significant enhancement of resistance switching was achieved with 5 at% Co doping in the films, and the possible switching mechanism was also discussed.